Ethical issues in forensic mental health research - Adshead, Gwen; Brown, Christine, 1968- (Forensic focus, 2003)
A contemporary case-based discussion of ethical dilemmas faced by researchers in forensic mental health, this book offers useful guidance to anyone planning research in this field. It focuses on problems frequently encountered, such as issues of capacity to consent in forensic settings and the meaning of consent to participate. Chapters cover issues such as the procurement of consent among incarcerated people; the ability of young people to provide consent; the effects of culturally specific lay beliefs about mental illness; confidentiality; multidisciplinary approaches; and ethics in risk ass.